Implementation of Niyyah Values to Increase Islamic Religious Education Students' Learning Motivation - Siti Fatmawati; Siti Fatimatuzzahro; Rifda Aulia; Tarsono Tarsono (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Problems in Islamic Religious Education (PAI) learning are often characterized by low student learning motivation, which is evident from the lack of participation, perseverance, and active involvement in the learning process. This condition indicates a gap between students' physical presence and mental and emotional involvement in learning. One effort that can be made is to internalize niyyah values as a spiritual foundation in learning. This study aims to analyze the implementation of niyyah values in PAI learning and their impact on student learning motivation. This study uses a qualitative method with a phenomenological approach, with PAI teachers and eighth-grade students at SMPN 2 Cileunyi Bandung as research subjects. Data collection techniques were carried out through observation, interviews, and documentation, while data analysis used the interactive model of Miles and Huberman which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of niyyah values carried out through the habit of straightening intentions, strengthening the meaning of worship in learning, and a reflective approach can increase students' intrinsic motivation. Students showed changes in attitude to be more active, diligent, and have a higher awareness of learning. Thus, the implementation of niyyah values has proven effective in increasing learning motivation while strengthening the holistic character formation of students in Islamic Education learning.